Who does private equity buy? E vidence on the role of private equity from buyouts of divested businesses - Kaul, Aseem; Nary, Paul; Singh, Harbir (Strategic Management Journal, 2018)
Research Summary: We examine the role of nonventure private equity firms in the market for divested businesses, comparing targets bought by such firms to those bought by corporate acquirers. We argue that a combination of vigilant monitoring, high‐powered incentives, patient capital, and business independence makes private equity firms uniquely suited to correcting underinvestment problems in public corporations, and that they will therefore systematically target divested businesses that are outside their parents’ core area, whose rivals invest more in long‐term strategic assets than their parents, and whose parents have weak managerial incentives both overall and at the divisional level. Results from a sample of 1,711 divestments confirm these predictions. Our study contributes to our understanding of private equity ownership, highlighting its advantage as an alternate governance form. Managerial Summary: Private equity firms are often portrayed as destroyers of corporate value, raiding established companies in pursuit of short‐term gain. In contrast, we argue that private equity investors help to revitalize businesses by enabling investments in long‐term strategic resources and capabilities that they are better able to evaluate, monitor, and support than public market investors. Consistent with these arguments, we find that when acquiring businesses divested by public corporations, private equity firms are more likely to buy units outside the parent's core area, those whose peers invest more in R&D than their parents, and those whose parents have weak managerial incentives, especially at the divisional level. Thus, private equity firms systematically target those businesses that may fail to realize their full potential under public ownership.